2015
DOI: 10.4236/aim.2015.513090
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Screening of Lactobacilli Isolates from Uttapam Batter Fermented Supplementing with <i>Piper betle</i> L. Leaves

Abstract: The in vitro screening of lactobacilli isolates from uttapam batter, fermented supplementing with Piper betle L. leaves, was performed in order to select potent isolates for probiotic use. Their resistance to simulated gastric and intestinal juices as well as their adhesion to epithelial intestinal HCT-15 and vaginal HeLa cell lines were assessed and also evaluated for their immunomodulatory ability in ex vivo condition. Isolates were able to adhere as well as reduce pathogen adhesion to monolayer cell lines' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In the case of LS1, LS2, and LS3, it is possible that cells were injured because the previous step (gastric phase), precluding a possible recovery (Madureira et al 2011;De Oliveira et al 2014). Dubey and Jeevaratnam (2015) and Das et al (2016) studied lactic bacteria for probiotic characterization that presented resistance to an acid environment and were similar to the results found in this study. Contrarily, Angmo et al (2016) reported variability in the survival of lactic acid bacteria exposed to gastric juice under simulated conditions in vitro, but with little or no impact on the viability of most of the strains studied, with L. casei being the most tolerant among all isolated LAB.…”
Section: Viability Of Lab Strains Under Simulated Gastrointestinal Trsupporting
confidence: 75%
“…In the case of LS1, LS2, and LS3, it is possible that cells were injured because the previous step (gastric phase), precluding a possible recovery (Madureira et al 2011;De Oliveira et al 2014). Dubey and Jeevaratnam (2015) and Das et al (2016) studied lactic bacteria for probiotic characterization that presented resistance to an acid environment and were similar to the results found in this study. Contrarily, Angmo et al (2016) reported variability in the survival of lactic acid bacteria exposed to gastric juice under simulated conditions in vitro, but with little or no impact on the viability of most of the strains studied, with L. casei being the most tolerant among all isolated LAB.…”
Section: Viability Of Lab Strains Under Simulated Gastrointestinal Trsupporting
confidence: 75%